1998
DOI: 10.1046/j.1365-2125.1998.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II antagonism and plasma radioreceptor‐kinetics of candesartan in man

Abstract: AimsThe pharmacodynamic properties of the angiotensin II antagonist candesartan in humans were assessed from the rightward shifts of angiotensin II dose-effect curves (Schild regression technique). The pharmacokinetic characteristics were determined by radioreceptor assay (r.r.a.) and h.p. ]-angiotensin II). Before and up to 24 h post dosing angiotensin II was infused in ascending dose steps until blood pressure (systolic and/or diastolic) increased by +25 mmHg. Individual angiotensin II dose-effect curves wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 16 publications
(23 reference statements)
0
32
0
Order By: Relevance
“…AT1 Receptor Blocker Pharmacology cilexetil administration in rats and dogs is 28 and 5%, respectively (Kondo et al, 1996). Radioreceptor assay techniques have yielded very similar estimates of pharmacokinetic parameters of candesartan as those obtained by classic analytical techniques (Malerczyk et al, 1998). Eprosartan is rapidly absorbed from the gastointestinal tract (t max 1-2 hours) with an absolute bioavailability of 13% (Tenero et al, 1998b).…”
Section: A Absorption and First-pass Metabolismmentioning
confidence: 62%
See 3 more Smart Citations
“…AT1 Receptor Blocker Pharmacology cilexetil administration in rats and dogs is 28 and 5%, respectively (Kondo et al, 1996). Radioreceptor assay techniques have yielded very similar estimates of pharmacokinetic parameters of candesartan as those obtained by classic analytical techniques (Malerczyk et al, 1998). Eprosartan is rapidly absorbed from the gastointestinal tract (t max 1-2 hours) with an absolute bioavailability of 13% (Tenero et al, 1998b).…”
Section: A Absorption and First-pass Metabolismmentioning
confidence: 62%
“…2) is not surprising. A similar apparent K i dose for candesartan (1.9 mg) had been determined by the same investigators in an earlier study (Malerczyk et al, 1998). A direct comparative study from another investigator group found that irbesartan produced greater inhibition of vasoconstriction and greater occupancy in the radioreceptor assay than losartan or valsartan when recommended starting doses of all three ARBs were compared , indicating that standard doses of three ARBs fall on different parts of the relative doseresponse curve.…”
Section: Antagonism In Vivomentioning
confidence: 73%
See 2 more Smart Citations
“…75,76 It has recently been shown that, in fact, all AT 1 -receptor antagonists are competitive antagonists, with tight-binding and very slow dissociation from the receptor. 77 This is especially true for candesartan, 78 which has demonstrated higher direct angiotensin II antagonistic activity in vivo than irbesartan, valsartan and losartan. 79,80 Thus, the effects of candesartan are likely to be long lasting and less easily overcome by increased endogeneous angiotensin II.…”
Section: Pharmacological Properties Of Candesartan Cilexetilmentioning
confidence: 99%